Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
[tex] \left \{ {{x=4y+6} \atop {x-3y=4}} \right. \\\\
4y+6-3y=4\\\\
y+6=4\ \ \ \ | subtract\ 6\\\\
y=-2\\\\
x=4y+6=4*(-2)+6=-8+6=-2[/tex]
You could use the substitution method (put x=4y+6 into x-3y=4):
4y+6-3y=4
Now you can combine alike terms
4y-3y=y
Put y into the first equation
Y+6=4
Now solve
Y+6=4
-6 -6
Y= -2
Now substitute y into the equation x=4y+6
X=4(-2)+6
Multiply 4x-2
X=-8+6
X= -2
The solution = (-2,-2)
4y+6-3y=4
Now you can combine alike terms
4y-3y=y
Put y into the first equation
Y+6=4
Now solve
Y+6=4
-6 -6
Y= -2
Now substitute y into the equation x=4y+6
X=4(-2)+6
Multiply 4x-2
X=-8+6
X= -2
The solution = (-2,-2)
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.